The detection of urethritis pathogens among patients with the male urethritis syndrome, genital ulcer syndrome and HIV voluntary counselling and testing clients: should South Africa's syndromic management approach be revised?. Issue 4 (11th January 2008) - Black, V; Magooa, P; Radebe, F; Myers, M; Pillay, C; Lewis, D A
Abstract : Objectives: To determine the prevalence of urethritis pathogens amongst male symptomatic urethritis (MUS) patients, genital ulcer (GUS) patients without urethritis symptoms and men requesting HIV testing at a voluntary counselling and testing (VCT) clinic. Methods: A prospective study was conducted in Johannesburg, South Africa. Men from the three groups were screened for urethritis pathogens using molecular tests. Culture for Neisseria gonorrhoeae and, initially, trichomoniasis was performed. Antimicrobial susceptibility testing was undertaken for ciprofloxacin on all gonococcal isolates; ciprofloxacin resistant isolates were screened for ceftriaxone resistance. Results: 664 participants were recruited (438 MUS, 76 GUS and 158 VCT) over 2 years. Gonorrhoea was detected in 62.3% MUS, 15.8% GUS and 3.2% VCT participants. Chlamydial infection was detected in 19.3% MUS, 13.2% GUS and 8.2% VCT participants. Trichomoniasis was detected in 4.9% MUS, 19.7% GUS and 3.8% VCT participants. Mycoplasma genitalium infection was detected in 14.4% MUS, 13.2% GUS and 7.0% VCT participants. Ciprofloxacin resistance increased from 13.0% in the first year to 26.3% in the second year; all resistant isolates were susceptible to ceftriaxone. Conclusions: Urethritis pathogens, including Trichomonas vaginalis, should be covered in syndromic management treatment of genital ulcers in the absence of clinical urethritis. Consideration should be given to adding metronidazole to existing MUS treatment. Ciprofloxacin can no longer be relied upon to treat presumptive gonococcal infections in South Africa.